Morphological Process of Food Lexicon after COVID-19 - Putu Wahyu Widiatmika (EDUCAFL : Journal of Education of English as Foreign Language, 2023)
The era of post COVID-19 has shown a shift of a lifestyle in terms of meal consumption among the people in the world. It is depicted from the creations of healthy and plant-based foods. This study is aimed to analyze the techniques of word formation about food and diet trends. The data of this study were new lexicons of food and diet trends taken from texts and scripts derived from different sources on the internet, such as news articles and blogs. The data were collected through documentation method with note-taking technique. Yule’s theory of word formation was applied to analyze the data with qualitative method. The result showed that the new food and diet lexicons are created with various techniques, such as compounding, blending, borrowing, clipping, and acronym. This study proves that linguistics, particularly morphology, is able to give contribution in the current trends of living.